(untitled) (Bioagro, 2025)
Pineapple (Ananas comosus) crop generates a high volume of harvest residues, resulting in significant environmental impact, primarily due to the large quantity of biomass left after fruit harvesting. This study aimed to evaluate fiber production and quality using two defibration methods, manual and mechanical, on leaves from three strata of MD2 pineapple plants subjected to different pre-conditioning techniques: soaking in water for 8 and 15 days, and NaOH solution for 1 hour. Results of this study demonstrated that 70 % of the leaves were suitable for defibration. The highest fiber yields were obtained from leaves in the middle and upper strata of the plants, with values of 8.98 and 12.4 g, respectively. The extraction time was shorter in the mechanical method, being 22 times more efficient than the manual method. The mechanical method favored fiber production when no prior conditioning of the leaves was performed, extracting an average of 50.5 g per plant. The manual method performed better when leaves were subjected to soaking in water or NaOH, extracting between 14.5 and 16.3 g per plant. Additionally, changes in the mechanical properties of the fiber were found to depend on the stratum of the plants and leaf pre-conditioning techniques. Our results contribute to explore the potential uses of fiber extracted by strata and highlight the possibilities of implementing pre-conditioning techniques.